Synthesis of Cu2O and ZnO Nanowires and their Heterojunction Nanowires by Thermal Evaporation: A Short Review - Muhammad Arif Khan; Samsudi Sakrani; Syahida Suhaima; Yussof Wahab; Rosnita Muhammad (Penerbit UTM Press, 2024)
One dimensional metal oxide semiconductor nanowires of copper (I) oxide (Cu2O), zinc oxide (ZnO), and their heterojunction nanowires possess remarkable physical and chemical properties. ZnO and Cu2O are attractive because the metals are abundant on earth, inexpensive, nontoxic. Moreover, these oxides have useful optical and electrical properties suitable for a wide variety of electrical devices, because their electrical conduction can be predictably controlled by doping. We here restrict the disscussion using a Hot Tube Vacuum Thermal Evaporation. The NWs in these devices will be studied by physical vapor deposition known as vapor-liquid-solid (VLS). Therefore, we explore conventional methods, particularly the VLS of growing ZnO and Cu2O nanowires which are assisted by the catalyst. In this short review, we report the individual and combined (Cu2O/ZnO) junction nanowires by PVD method. The main advantages of these composite nanowires are the natural p-n characteristics, the broad light absorption, the high sensitivity to humidity changes, and the fast dynamic response. The combination of all characteristics offered by Cu2O/ZnO nanowires can enable the fabrication of diverse sensing devices, and photovoltaic solar cells.